The Human “Cochlear Battery” – Claudin-11 Barrier and Ion Transport Proteins in the Lateral Wall of the Cochlea - Liu, Wei; Schrott-Fischer, Annelies; Glueckert, Rudolf; Benav, Heval; Rask-Andersen, Helge (Frontiers in Molecular Neuroscience, 2017)
Background: The cochlea produces an electric field potential essential for hair cell transduction and hearing. This biological “battery” is situated in the lateral wall of the cochlea and contains molecular machinery that secretes and recycles K+ ions. Its functioning depends on junctional proteins that restrict the para-cellular escape of ions. The tight junction protein Claudin-11 has been found to be one of the major constituents of this barrier that maintains ion gradients (Gow et al. 2004, Kitajiri et al. 2004). We are the first to elucidate the human Claudin-11 framework and the associated ion transport machinery using super-resolution fluorescence illumination microscopy (SR-SIM). Methods: Archival cochleae obtained during meningioma surgery were used for SR-SIM together with transmission electron microscopy after ethical consent. Results: Claudin-11-expressing cells formed parallel tight junction lamellae that insulated the epithelial syncytium of the stria vascularis and extended to the suprastrial region. Intercellular gap junctions were found between the barrier cells and fibrocytes Conclusions: Transmission electron microscopy, confocal microscopy and SR-SIM revealed exclusive cell specialization in the various subdomains of the lateral wall of the human cochlea. The Claudin-11-expressing cells exhibited both conductor and isolator characteristics, and these micro-porous separators may selectively mediate the movement of charged units to the intrastrial space in a manner that is analogous to a conventional electrochemical “battery.” The function and relevance of this battery for the development of inner ear disease are discussed.